#### Answer

$- \text{ } \text{ } \text{ } 6$

#### Work Step by Step

RECALL:
The perfect square trinomial $a^2-2ab+b^2$ can be factored using the formula:
$a^2-2ab+b^2=(a-b)^2$
The given trinomial can be written as:
$=x^2-2(x)(6)+6^2$
This trinomial above is a perfect square trinomial which can be factored using the formula given above.
Factor using the formula above with $a=x$ and $b=6$ to obtain:
$=(x-6)^2$
Thus, the missing expression in the given statement is:
$- \text{ } \text{ } \text{ } 6$